Cambridge English: Proficiency 1 with answers. Authentic examination papers from Cambridge ESOL (Cambridge, Cambridge University Press, 2012)
This ist collection of examination papers for updated Cambridge English: Proficiency, also known as Certificate of Proficiency in English (CPE), provides all the exam practice you need. It contains: four official examination papers that provide authentic exam practice a helpful overview of the Cambridge English: Proficiency exam to familiarise you with its format attractive visual material to help you practise for the paired Speaking test photocopiable answer sheets so you can practise transferring your answers. This'with answers' edition also includes: a clear explanation of marking and grading, illustrated by authentic sample answers recording scripts and answer keys frameworks to help you prepare for the Speaking test.